Enhancement of tetracycline removal in aquatic environment by nano-pyrite/H_2 O_2/ultrasound as a sono-Fenton process - Elham Aseman-Bashiz; Hossein Sayyaf (Journal of Water and Environmental Nanotechnology)
This study was conducted with the aim of introducing a new sono-Fenton system containing nano-pyrite catalyst and hydrogen peroxide (HP) for the effective removal of tetracycline (TC) from aqueous solutions. The synthesized nano-pyrite was characterized through XRD, FTIR, FE-SEM, and EDX analyses. The best performance of the sono-Fenton nano-pyrite/HP system was observed under the condition of pH 3.0, TC 8.0 mg/L, HP 4.0 mM, ultrasound (US) 40 W, nano-pyrite 1.0 g/L, and 20 min with 93.1% removal efficiency. Comparison of the efficiency of the proposed system components confirmed the remarkable synergy between sono-catalysis and Fenton reactions due to the simultaneous application of nano-pyrite, HP, and US power. Meanwhile, US irradiation caused fluidization, turbulence, mass transfer, and nano-pyrite surface cleaning due to its cavitation and oscillation effects. According to the tracer test, the main agent of TC degradation in the sono-Fenton process was HO^•. The results showed that the TC removal efficiency from the first to the fourth run reached from 93.1% to 70.3%. This means that the recyclability of nano-pyrite has been very successful. Overall, the proposed sono-Fenton system was an efficient and sustainable process for the rapid and effective removal of pharmaceutical contaminants from water and wastewater.